Ensino de leitura na escola e trajetórias de letramento de professores de língua portuguesa: um estudo de caso. - Pereira, Silvia Letícia Matievicz (2007)
From the premise that school is, in the nowadays society, the main agency of literacy (KLEIMAN, 1995), that the teacher is an agent of literacy (KLEIMAN, 2006), and that reading is a way to democratize the cultural heritage of people (SOARES, 2006), this dissertation considers the configuration that takes place during the teaching of reading at school. This dissertation considers also the problematic of the relation between the practices of literacy developed by the Portuguese language teachers in the classroom and the trajectories of literacy of the same teachers. It is considered the fact that the focus of singularity of these trajectories can reveal important elements for the understanding of the school practice of literacy, specially when we refer to the teaching of reading as shown by Vóvio and Souza (2005). The research follows the paradigms of a qualitative survey in Education, developing a case study in the Public State School in the city of Cascavel Paraná, which had the best result with the 8th grade in the reading evaluation SAEB in the year 2005. For the field work, the principles of an Ethnographic survey were used (ERICKSON, 1989, 1990; ANDRÉ, 1995), For the investigation of the literacy trajectory of the Portuguese language teachers in the referred school, the principles of Oral History (ROBERTS, 2002, ALBERTI, 2005) were adequate. The analysis of reading practices developed by the teachers participating of this investigation were necessary and they seem to evidence that they are based in a conception of language and consequently of reading - turning the structural patterns and to the autonomous model of literacy (STREET, 1995). The results would reveal a lack of knowledge in relation to a great number of theories concerning reading. Also these professionals seem to offer a limited forms of legitimate literate culture to their students. Listening to the histories about the trajectories of literacy of these professionals, the evidences merged from the analysis observed, showed, above all, the exclusion or the partial inclusion (BATISTA, 1998), of the participants of these research to the literacy practice considered legitimate, as well as the consequent appropriation of the valued of literate culture. The results seem to show that these teachers did not do a satisfactory work with reading in their classes. It happens because they did not have at their disposal - and even do not dispose of conditions to access the cultural values considered legitimate. This means that the possibilities of intersection between the practices they developed practices and trajectories that they lived.